Condutividade hidráulica de misturas solo-cimento compactas submetidas à ação de lixiviados ácidos em ensaios de longa duração - Tímbola, Rafael de Souza (2014)
The present study was designed to contribute to the general understanding of the long-term hydraulic behavior of compacted clayey soils when in contact with highly acidic leachates, aiming at the application in bottom barriers for industrial and mining solid waste disposal facilities. Long term hydraulic conductivity tests were performed on a rigid wall column apparatus in specimens molded with various amounts of Portland cement (0, 1 and 2%) and dry unit weights (14.5, 15.0, and 15.5 kN/m3), following a factorial experimental design with center points. The soil was a typical Latosol from Passo Fundo/RS. During these tests, a constant vertical static load of 280 KPa was applied, seeking to simulate an overload of waste or tailings over the barrier. The percolated solution was prepared to a volume concentration of 2% of sulfuric acid in distilled water. Prior to the acidic percolation, the specimens were percolated with distilled water until the steady flow was reached. All specimens were percolated a least 15 volumes of voids, being approximately 5 volumes of distilled water. The results showed a considerable reduction in hydraulic conductivity of the compacted mixtures when percolated with the acidic solution, although all specimens reached values less than 10-9m/s to the stage of acid percolated. Both control factors investigated in the experimental program (cement content and dry unit weight) significantly influenced the hydraulic conductivity, and the upper values of these factors (2 % cement and dry unit weight of 15.5 kN/m3) determined the lower hydraulic conductivity. The static vertical load applied to the specimens may have contributed to the reduction in voids ratio and consequently to the reduction of hydraulic conductivity in the long term